(Re-)sources of innovation: Understanding and comparing time-spatial innovation dynamics through the lens of communities of practice. (October 2015) - Müller, Felix C.; Ibert, Oliver
Highlights: The authors develop a systematic typology of knowing in practice. The typology embraces epistemic, creative, professional and interest-driven knowing. The authors suggest a dynamic approach to a spatial analysis of innovation. Knowing in practice is treated as origin of innovation and context of translation. The typology captures systematic differences in trajectories of innovation. Abstract: Communities of practice play an important role in innovation processes. It is, however, still unclear what their particular function is. In this article the authors seek first to develop further systematic differentiations between different types of knowing in practice to provide the conceptual ground for studying the influences of knowing in practice on innovation in a comparative way. Therefore, existing inductive approaches are complemented with deductive elements that highlight different impulses of reflexivity (push vs. pull) and different internal logics of reflexivity (rationalist vs. aesthetic). Second, in this article the authors introduce a dynamic approach which focuses on core ideas of innovation processes from a spatial perspective. In such a dynamic view types of knowing in practice have an impact as sources and resources of innovation. As sources of innovation they form a particular locus in which novel ideas emerge and subsequently take particular trajectories. As resources of innovation they intervene at subsequent stages of the process and propel further the translation process of a novel idea becoming eventually a valuable and practicable solution.